Making money from money : the world of currencies - Lydon, Tom, 1960- (Pearson Education Pub. as FTPress Delivers, 2010)
"What you need to know about currency trading-and how to use currency ETFs to profit from it. If you liked this Element, read more from Tom Lydon, including The ETF trend following playbook: profiting from trends in bull or bear markets with exchange traded funds (ISBN: 9780137029013)"--Resource description page.